2021
DOI: 10.1038/s41587-021-00986-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mapping of a whole rhesus monkey brain at micrometer resolution

Abstract: Whole-brain mesoscale mapping of primates has been hindered by large brain size and the relatively low throughput of available microscopy methods. Here, we present an integrative approach that combines primate-optimized tissue sectioning and clearing with ultrahigh-speed, large-scale, volumetric fluorescence microscopy, capable of completing whole-brain imaging of a rhesus monkey at 1 µm × 1 µm × 2.5 µm voxel resolution within 100 hours. A progressive strategy is developed for high-efficiency, long-range traci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 63 publications
0
67
0
Order By: Relevance
“…These are both key cell types implicated in neurodegenerative disorders 52,53,73,74 , and the experiments shown here open the door for comparing these cell types in diseased and healthy macaques. Moving forward, the work here will enable major efforts under the NIH BRAIN Initiative 75 , as CAP-Mac-mediated labeling can be readily combined with tissue clearing and imaging techniques to map long-range projections within the Old World primate connectome [76][77][78] . Such studies present a novel opportunity to study the macaque brain, and more generally, an opportunity to understand the inner workings of the primate CNS.…”
Section: Discussionmentioning
confidence: 99%
“…These are both key cell types implicated in neurodegenerative disorders 52,53,73,74 , and the experiments shown here open the door for comparing these cell types in diseased and healthy macaques. Moving forward, the work here will enable major efforts under the NIH BRAIN Initiative 75 , as CAP-Mac-mediated labeling can be readily combined with tissue clearing and imaging techniques to map long-range projections within the Old World primate connectome [76][77][78] . Such studies present a novel opportunity to study the macaque brain, and more generally, an opportunity to understand the inner workings of the primate CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that our resolution (2 mm) was not fine enough to capture the finer scaled regularities of connectivity, including columnar (Cavada and Goldman-Rakic, 1989;Schwartz and Goldman-Rakic, 1984;Selemon and Goldman-Rakic, 1988;Seltzer et al, 1996), laminar (Barbas, 2015), and layer-specific, stripe-like (Levitt et al, 1993;Lund et al, 1993) patterns observed in tracing studies. High-resolution fMRI (Huber et al, 2017;Yacoub et al, 2020) and ultrafast whole-brain fluorescence imaging (Xu et al, 2021) in primates will help better link connectivity patterns mapped by EM-fMRI and tracing in the future.…”
Section: Strengths and Limitations Of Dense Connectivity Mapping Using Em-fmrimentioning
confidence: 99%
“…All tissue-clearing protocols should be understood as modular toolboxes in which specific steps can be added or removed in order to adapt them to specific applications; for example, modules taken from the CUBIC and CLARITY pipelines have recently been combined to clear slices of a rhesus monkey brain (Xu et al, 2021). Most clearing protocols can be broken down to into six modules: fixation, lipid removal or delipidation, decalcification (optional), bleaching or depigmentation/decolorization (optional), labeling (optional) and optical clearing (Fig.…”
Section: Common Modulesmentioning
confidence: 99%